Exploration of Opportunities and Challenges of Technology-based Mathematics Teaching: Students and Teachers Perspectives - Ghimire, Shree Prasad; Paudel, Krishna Chandra (Mathematics Education Forum Chitwan, 2024)
The pervasive integration of Information and Communication Technology (ICT) in education necessitates systematic investigation of its practical effectiveness in mathematics instruction, as empirical evidence of its impact on teaching and learning processes remains crucial for enhancing pedagogical practices. This study investigated the opportunities and challenges of ICT integration in mathematics instruction among Bachelor of Education (B.Ed.) students majoring in mathematics and their teachers at Tribhuvan University. The information/data was gathered through interviews with eight students and four teachers who had studied and taught for various years (first, second, third, and fourth) using interpretative phenomenological techniques. From the study, it was found that high motivation, self-paced learning, conceptual understanding of contents, anytime-anywhere learning, opportunities for repeated learning, and feedback were the fundamental opportunities in the use of ICT. Furthermore, insufficient prior knowledge and skills on ICT use by both students and teachers, insufficient class time, less knowledge to prepare the course materials, less supportive infrastructure, insufficient access to ICT devices with internet, and availability of freely available software were found the challenges on the use of ICT.